Long‐term outcomes of entecavir monotherapy for chronic hepatitis B after liver transplantation: Results up to 8 years. Issue 4 (26th August 2017) - Fung, James; Wong, Tiffany; Chok, Kenneth; Chan, Albert; Cheung, Tan‐To; Dai, Jeff Wing‐Chiu; Sin, Sui‐ling; Ma, Ka‐Wing; Ng, Kelvin; Ng, Kevin Tak‐Pan; Seto, Wai‐Kay; Lai, Ching‐Lung; et al.
Abstract : Long‐term antiviral prophylaxis is required to prevent hepatitis B recurrence for patients with chronic hepatitis B after liver transplantation. We determined the long‐term outcome of 265 consecutive chronic hepatitis B liver transplant recipients treated with entecavir monotherapy without hepatitis B immune globulin. Viral serology, viral load, and liver biochemistry were performed at regular intervals during follow‐up. The median duration of follow‐up was 59 months. The cumulative rates of hepatitis B surface antigen (HBsAg) seroclearance were 90% and 95% at 1 and 5 years, respectively. At 1, 3, 5, and 8 years, 85%, 88%, 87.0%, and 92% were negative for HBsAg, respectively, and 95%, 99%, 100%, and 100% had undetectable hepatitis B virus (HBV) DNA, respectively. Fourteen patients remained persistently positive for HBsAg, all of whom had undetectable HBV DNA. There was no significant difference in liver stiffness for those who remained HBsAg‐positive compared to those who achieved HBsAg seroclearance (5.5 versus 5.2 kPa, respectively; P = 0.52). The overall 9‐year survival was 85%. There were 37 deaths during the follow‐up period, of which none were due to hepatitis B recurrence. Conclusion: Long‐term entecavir monotherapy is highly effective at preventing HBV reactivation after liver transplantation for chronic hepatitis B, with a durable HBsAg seroclearance rate of 92%, an undetectable HBV DNA rate of 100% at 8 years, and excellent long‐term survival of 85% at 9 years. (Hepatology 2017;66:1036‐1044).